Cytokine levels in major depression are related to childhood trauma but not to recent stressors. (November 2016) - Grosse, Laura; Ambrée, Oliver; Jörgens, Silke; Jawahar, M. Catharine; Singhal, Gaurav; Stacey, David; Arolt, Volker; Baune, Bernhard T.
Highlights: Stress over lifetime was studied for effects on cytokine levels in major depression. Serum TNF-α and IL-6 levels were associated with childhood trauma. Severity of childhood sexual abuse was related to increased TNF-α and IL-6 levels. Serum TNF-α and IL-6 levels were not related to recent stressful life events. Stress during susceptible life periods may prime for long-term effects on immunity. Abstract: Background: Major depressive disorder (MDD) is a stress-related psychiatric disorder. A subgroup of MDD patients is characterized by increased inflammatory activation. We aimed to investigate whether increased inflammation particularly occurs in MDD patients with a history of stressful early or later life experiences. Methods: Serum levels of tumor necrosis factor alpha (TNF-α) and interleukin (IL)-6 were determined in N  = 214 MDD patients and N  = 180 healthy controls (HC). Childhood trauma (Childhood Trauma Questionnaire – CTQ), adverse life events of the past 12 months (List of Threatening Experiences Questionnaire – LTE-Q), and perceived stress in the past month (Perceived Stress Scale – PSS) were analyzed with regard to cytokine levels. Results: Pro-inflammatory cytokine levels were not related to global scores of adverse events or perceived stress covering different time points ranging from childhood to the past month. However, in the subgroup of traumatized MDD patients, higher severity of childhood sexual abuse was associated with higher levels of both IL-6 and TNF-α in a linear fashion. Conclusions: Our data suggest a linear relationship between childhood sexual abuse and increased pro-inflammatory cytokine levels in MDD patients, while more recent stressful life events were not related to these inflammatory markers.